Complete Resolution of Pseudomalignant Erosion in a Reflux Gastroesophageal Polyp with Proton Pump Inhibitor. (24th November 2015) - Nakajima, Takahiko; Yagi, Haruo; Baba, Hayato; Minamisaka, Takashi; Miwa, Shigeharu; Hayashi, Shinichi; Nishida, Takeshi; Hatta, Hideki; Tsuneyama, Koichi; Imura, Johji
Abstract : Pseudomalignant erosion is a diagnostic pitfall for pathologists in the differential diagnosis of malignant neoplasms. Here, we present a challenging case of a biopsy specimen from the eroded head of a polyp at the esophagogastric junction. A malignant neoplasm could not be ruled out due to the presence of bizarre stromal cells. A second biopsy performed after the administration of a proton pump inhibitor (PPI) for 4 weeks revealed endoscopic resolution of the polyp along with the complete histological resolution of the bizarre stromal cells and led to the diagnosis of pseudomalignant erosion in a reflux gastroesophageal polyp. In conclusion, histological and endoscopic response to PPI therapy is an important clue for the correct diagnosis of reflux gastroesophageal polyps with pseudomalignant erosion.